Kajian Mutu Kimia Bubuk Kopi Espresso Aceh Berdasarkan Rasio Pencampuran Varietas Kopi Arabika dan Robusta dan Teknik Penyangraian - Dian Hasni; Murna Muzaifa; Dedy Rahmad; Maulana Insan (REACTOR: Journal of Research on Chemistry and Engineering, 2021)
Generally there are two coffee varietes cultivated in Indonesia, known as Arabica and Robusta coffee. Arabica distinctively known for its distinctive quality but limited quantity compared to robusta which is commonly use for commercial coffee production due to its robust productivity. Nowadays, global market demand encourages a huge variety of coffee product, based on coffee such as espresso. The quality of espresso is influence by many factors such as roasting technique and ratio blending of coffee ground. This study aims to determine the influence of blending ratio and roasting techniqus to the chemical compounds of coffee ground and its espresso brewed. This research used Factorial Random Design, consists of 2 factors. First factor is ratio of blending Arabica and Robusta with three levels ratio; B1=70:30; B2=80:20; and B3=90:10). The second factor is roasting technique, consisting of 2 levels of conventional roasting(P1) and torrefacto (P2). Each treatment was repeated 3 replications to obtain 18 units of experiment. Measured parameters are pH of brewed espresso and moisture (%), ash (%), protein (%), lipid (%) and caffeine (%) contents of coffee ground. The results showed that the blending ratio was highly significant (P≤0,01) to the moisture and protein contents of coffee grounds and pH of resulted espresso. The best treatment was obtained from combination of B1P1 treatment (combination blending ratio (70%:30%) and conventional roasting) with 2.00% moisture content, 4.83% ash, 13.04% protein, 10.41% fat, 81.17% carbohydrate and caffeine 1.49%.